Genetic alterations in the molecular subtypes of bladder cancer: Illustration in the Cancer Genome Atlas dataset - Choi, W; Ochoa, A; McConkey, D; Aine, M; Höglund, M; Kim, W; Real, F; Kiltie, A; Milsom, I; Dyrskjøt, L; Lerner, S (Elsevier, 2017)
Context Recent whole genome mRNA expression profiling studies revealed that bladder cancers can be grouped into molecular subtypes, some of which share clinical properties and gene expression patterns with the intrinsic subtypes of breast cancer and the molecular subtypes found in other solid tumors. The molecular subtypes in other solid tumors are enrichedwith specificmutations and copy number aberrations that are thought to underlie their distinct progression patterns, and biological and clinical properties. Objective The availability of comprehensive genomic data from The Cancer Genome Atlas (TCGA) and other large projects made it possible to correlate the presence of DNA alterations with tumor molecular subtype membership. Our overall goal was to determine whether specific DNA mutations and/or copy number variations are enriched in specific molecular subtypes. Evidence We used the complete TCGA RNA-seq dataset and three different published classifiers developed by our groups to assign TCGA’s bladder cancers to molecular subtypes, and examined the prevalence of the most common DNA alterations within them. We interpreted the results against the background of what was known from the published literature about the prevalence of these alterations in nonmuscle-invasive and muscle-invasive bladder cancers. Evidence synthesis The results confirmed that alterations involving RB1 and NFE2L2 were enriched in basal cancers, whereas alterations involving FGFR3 and KDM6A were enriched in luminal tumors. Conclusions The results further reinforce the conclusion that the molecular subtypes of bladder cancer are distinct disease entities with specific genetic alterations. Patient summary Our observation showed that some of subtype-enriched mutations and copy number [6TD$DIF]aberrations are clinically actionable, which has direct implications for the clinical management of patients with bladder cancer.